Uma proposta de tomada inteligente visando a eficiência energética em redes e ambientes domésticos - SOUZA, Arlisson da Silva (2016)
Energy failure is one of the biggest global concerns on economic growth. Technological advances and the increased purchasing power of the population increase energy consumption. Thus, the rational use of energy is one of the goals to be achieved by countries. In Brazil, one of the recent bets for reducing consumption in the residential sector is the shutdown of electronic devices in order standby. This mode is characterized by the standby state in which the electronic devices waste energy even not performing its main functions, in order to get the comfort of quick reclosing of the equipment or facilities as the drive via remote control. However, many users are unaware that the equipment standby increase the total electricity consumption in a residence. It was concerned that energy consumption in the residential sector the Brazilian Business Council for Sustainable Development has recommended the creation of intelligent sockets can automatically turn off devices when they acionarem mode standby, making the practical and transparent process for the user. While there are some solutions in this sense in the existing market outlets are static, unable to learn environmental behavior and usually have no interaction with the user. Thus, this paper proposes an outlet with intelligent management in order to maximize the energy efficiency of electronic devices in order standby, from the use of presence and current sensors. Therefore, there was the integration of a case-based reasoning system (RBC) to a supervisory system, this on a wireless sensor network whose purpose is to infer profiles of use of electronic devices in the environment. In the construction of the prototype we used free open source technology as Radiuino for wireless sensor network, the ScadaBR as supervisory system and the framework JCOLIBRI for implementation of RBC. The prototype has been validated for 7 (seven) days in a typical Brazilian residence of two (2) rooms, having 2 (two) televisions, one (1) video game and one (1) HD decoder pay television. After the validation experiment, there was a reduction of 10.27 kWh per month, or an R economy $ 5.11 per month on energy bill of a residence. It is estimated that if the prototype is applied to all households by the initiative of the Federal Government, the large-scale savings would be approximately 201 million kWh, considering only the shutdown standby HD decoder. This fact would reduce the energy needs of the country and the consequent reduction of tariff rates applied to the consumer. Furthermore, it is an economically viable proposal by its cost relative to their market alternatives, in addition to the ongoing return on investment in 12 months.